Influence of APOA5 (rs662799 and rs3135506) gene polymorphism in acute myocardial infarction patients and its association with basic coronary artery disease risk factors - Rohit Kumar Srivastava, Pratibha Singh, Pratima Verma, Rishi Sethi, Arti Verma, Wahid Ali, Sunita Tiwari (Journal of Applied Pharmaceutical Science, 2015)
The aim of this study was to examine the allele and genotype of APOA5 -1131T/C (rs662799) and APOA5-56C/G (rs3135506) gene in acute myocardial (AMI) case and control subjects. 304 case and 304 controls were enrolled in this study. DNA was extracted using salting out method followed by polymerase chain reaction amplification and restriction endonuclease digestion (using MseI for -1131T/C and Taq1 for -56C/G). Digested PCR products were identified using agarose gel electrophoresis and stained with ethidium bromide. There was a strong association between APOA5 -1131T/C (TC vs. TT, OR= 1.58 and CC vs. TT OR= 2.43) and APOA5 -56C/G (CG vs. CC, OR= 1.64 and GG vs. CC, OR= 2.44) polymorphisms with AMI. Out of the six potential risk factors for coronary artery disease, only smoking, diabetes and hypertension were found to be associated with APOA5 gene and increased the risk of AMI. Smoking was the most prominent risk factor for both the genes. Other risk factors like history of dyslipidemia, obesity and family history of coronary artery disease did not reveal any potential association with the candidate gene. Our data demonstrate that both the SNPs in the APOA5 gene (-1131T/C, and -56C/G) were strongly associated with AMI in north Indian population.
Keywords: Atherosclerosis, Single nucleotide polymorphism, Genetic variability, Cigarette smoking, Apolipoprotien gene.